Critical reflections on the formation of the social subject in a program of higher education - Torres Merchán, Nidia Yaneth; Pachón Barbosa, Néstor Adolfo; Medina Peña, Nelson Augusto; Amézquita Vargas, Juan Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This reflection article discusses the importance of formation spaces concerning social subjects. These considerations are established from the theoretical referents of the topic and the analysis of the perceptions gathered in questionnaires filled in by some graduates in Bachelor of Natural Sciences and Environmental Education degree. This favors the assessment of some limitations of the academic program implicit in their career, their experience, and daily practices. Therefore, it is required to reflect and question pedagogical practices happening in the training of these teachers based on ongoing communication with graduates.